2023
DOI: 10.18632/aging.204514
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum total cholesterol level and bone mineral density in older adults

Abstract: Background: Osteoporosis is a major clinical problem in elderly men and women. The correlation between total cholesterol and bone mineral density remains controversial. NHANES is the cornerstone for national nutrition monitoring to inform nutrition and health policy. Methods: Sample sizes and the location of the study and the time when it was conducted: we obtained 4236 non-cancer elderly from NHANES (National Health and Nutrition Examination Survey) database from 1999 to 2006. Data were analyzed with the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, a study utilizing NHANES data acquired from 2011 to 2018 in the United States demonstrated that serum TC was inversely correlated with BMD among men aged 20–59 years [ 5 ]. A study of cancer-free older adults in the United States revealed a significant negative correlation between serum TC levels and lumbar BMD in men aged > 60 years [ 4 ]. The reason for this difference may be the difference in eating habits and lifestyles between Asians, Europeans, and Americans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study utilizing NHANES data acquired from 2011 to 2018 in the United States demonstrated that serum TC was inversely correlated with BMD among men aged 20–59 years [ 5 ]. A study of cancer-free older adults in the United States revealed a significant negative correlation between serum TC levels and lumbar BMD in men aged > 60 years [ 4 ]. The reason for this difference may be the difference in eating habits and lifestyles between Asians, Europeans, and Americans.…”
Section: Discussionmentioning
confidence: 99%
“…A preclinical study using quantitative computed tomography in mice found that a high-cholesterol diet can lead to low bone content [ 3 ]. Research based on data from the US National Health and Nutrition Examination Survey (NHANES) database has shown that TC is inversely associated with lumbar bone mineral density (BMD) in older non-cancer individuals aged ≥ 60 years [ 4 ]. Another study discovered a correlation between low TC levels and reduced total BMD in young adults aged 20–29 years; in individuals aged 40–49 years and those with borderline diabetes, a non-linear curve associating TC with total BMD was identified, with an inflection point at 4.65 mmol/L and 6.7 mmol/L, respectively [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…( 37 )Hu et al. (, 38 ). In recent years, there has been an increasing number of MR studies that have examined the causal relationship between lipid metabolism and bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, an increasing number of studies have demonstrated a close correlation between lipid metabolism and bone metabolism, although the conclusions remain debatable. HDL-C, acknowledged as "good" cholesterol with cardiovascular protectionJomard and Osto ( 23 38). In recent years, there has been an increasing number of MR studies that have examined the causal relationship between lipid metabolism and bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Data on association between lipid status and the efects of hypolipidemic therapy on bone metabolism is mixed. Both a negative relationship between total cholesterol and low-density lipoprotein cholesterol concentrations and BMD [153][154][155][156][157][158] and a positive association between high-density lipoprotein cholesterol and BMD [159] have been reported. Other studies, however, found that higher serum high-density lipoprotein cholesterol and apolipoprotein B levels (traditionally viewed as a protective for CVD factor) reduced BMD and may increase the risk of osteoporotic fracture (including HF) independently of traditional risk factors for fractures [160][161][162][163][164][165][166].…”
Section: Prognostic Value Of Ckd and Related Factors For Predictingmentioning
confidence: 99%